Advanced lead acid battery desulfators - Guo, Sheng. (2010)
Lead-acid battery has been found for more than 150 years, and it is now commonly used in our daily life from motor vehicles to electronic devices. The common problem for the lead-acid batteries is called sulfation which will decrease battery life. However, sulfation can be reversed and prolong the battery life by using and electronic device called desulfator.